2011
DOI: 10.1111/j.1750-3841.2011.02421.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative GC/MS Analysis of Essential Oils Extracted by 3 Methods from the Bud of Citrus aurantium L. var. amara Engl

Abstract: C. aurantium oils from different plant parts have great economic, medicinal, and nutritional values because of their wide-spectrum biological activities. The essential oil from C. aurantium L. var amara is one of the best C. aurantium oils. The data presented in this article will help us understand the relationship between essential oils and its extraction methods and know more about the aromatic components of Citrus aurantium bud. The methods established in this study will provide useful reference information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Prostaglandin F 2 alpha (PGF 2 a), phenylephrine (PE), 1H- [1,2,4] oxadiazolo [4,3-a] quinoxalin-1-one (ODQ), 2-aminoethoxydiphenyl borane (2-APB), tetraethylammonium chloride (TEA), 2,5-di-t-butyl-1,4-benzohydroquinone (BHQ), Hydralazine hydrochloride, Ni 2+ , verapamil, acetylcholine (ACh), and ruthenium red were from Sigma (St. Louis, MO). N G -Nitro-L-arginine-methyl ester (L-NAME) was obtained from Alexis Biochemicals (San Diego, CA).…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostaglandin F 2 alpha (PGF 2 a), phenylephrine (PE), 1H- [1,2,4] oxadiazolo [4,3-a] quinoxalin-1-one (ODQ), 2-aminoethoxydiphenyl borane (2-APB), tetraethylammonium chloride (TEA), 2,5-di-t-butyl-1,4-benzohydroquinone (BHQ), Hydralazine hydrochloride, Ni 2+ , verapamil, acetylcholine (ACh), and ruthenium red were from Sigma (St. Louis, MO). N G -Nitro-L-arginine-methyl ester (L-NAME) was obtained from Alexis Biochemicals (San Diego, CA).…”
Section: Chemicalsmentioning
confidence: 99%
“…amara and other Citrus species, is rich in limonene and linalool [4]. It has been widely used in humans for managing anxiety and stress because of its relaxing effect, for instance during labor [5].…”
Section: Introductionmentioning
confidence: 99%
“…The separation of flavonoids and essential oil from C. aurantium var amara have generated widespread interest (Jiang, Yang, Zhu, Piao, & Jiang, 2011;Liu, Chen, Huang, Yu, & Qiu, 2009). However, the significant components have not been clarified yet, and multi-activity tests of 45 of these constituents from C. aurantium var amara have not been particularly examined so far.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils of widely well-known citruses, sweet orange, grapefruit, mandarin, lemon, lime, bitter orange, and bergamot, had been analyzed quantitatively [2]. Recently, the technique has also been applied to the composition analysis of essential oils obtained from different citrus varieties such as Tunisian citrus [3], Diamante peel [4], bitter orange [5], and commercially available citrus essential oils [6]. Results indicated that citrus essential oil consists of mostly aromatic components such as monoterpene, sesquiterpene, and some oxygenated compounds.…”
Section: Introductionmentioning
confidence: 99%